Implementation of Differentiated Instruction in Realizing Inclusive Learning in Primary Schools - Fuji Lestari; Nurul Fadhilah; Amalia Tasya (Ludi Litterarri, 2025)
Inclusive learning in elementary schools emphasizes accessibility and diversity in education, ensuring that all students can learn without discrimination. Differentiated Instruction (DI) is an important approach in supporting inclusive learning by adjusting teaching methods based on students' needs, interests, and learning styles. However, the implementation of DI still faces various challenges, such as lack of teacher understanding, limited resources, and education policies that do not support curriculum flexibility. This study uses a literature study method to analyze the implementation of DI in inclusive learning in elementary schools. The results of the analysis show that the implementation of DI can improve student motivation and academic outcomes, but requires teacher readiness through ongoing training and more flexible policy support. In addition, the integration of learning technology can help overcome the constraints of differentiation in heterogeneous classes. Therefore, synergy is needed between the government, schools, and the education community in providing resources and regulations that support the success of DI. With the right strategy, DI has the potential to create a more inclusive, adaptive, and effective learning environment in improving the quality of elementary education